KEBIJAKAN INDONESIA DALAM MERESPON MASUKNYA SAMPAH ELEKTRONIK DARI SINGAPURA - Irna Yani; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study aims to explain the policies taken by Indonesia in responding to the entry of electronic waste from Singapore. Because e-waste processing costs a lot of money and must follow established policy procedures, Singapore tends to send its e-waste to developing countries, including Indonesia. Electronic waste that enters the territory of Indonesia is then processed or recycled in a very simple way and does not follow established policy procedures. Of course, this has a dangerous impact on environmental conditions and public health. This study uses Interdependence Liberalism perspective which explains that military power is a less useful instrument and welfare is the dominant goal of countries in the world. The method used in this research is a descriptive qualitative method. Data collection techniques through document analysis or secondary data analysis, such as books, journals, documents, reports, and websites. From the results of the study, that Indonesia's efforts to overcome the entry of electronic waste from Singapore in 2012-2020 has decreased. Even though in the implementation of these policies there are still irresponsible elements found. This happens because of the weak law enforcement in Indonesia and the lack of awareness of the Indonesian people about the harmful effects of electronic waste. Keywords: Electronic Waste, Policy, Indonesia, dan Singapore.